The expression of yoeb and pezt bacterial toxin genes in microalga Chlorella vulgaris and the effects on cell viability / Ng Shet Lee - Ng , Shet Lee (2017)
Chlorella vulgaris is an oleaginous microalgae which is a potential candidate for the harvesting of valuable cellular contents, particularly for the production of biofuels. However, the microalgae’s rigid cell wall proved to be a challenge faced during microalgae transformation as well as the downstream harvesting of cellular contents. Toxin-antitoxin (TA) systems are genetic entities that are almost ubiquitous in prokaryotic genomes and have been implicated in programmed bacterial cell death and to date, no TA homologs are found in eukaryotic cells. A TA system is usually made up of two genes, an antitoxin gene that encodes a labile antitoxin, which can either be an untranslated RNA or a protein, and the toxin gene which encodes for the more stable toxin protein. The expression of several TA toxins were reported to be functionally lethal in several eukaryotic organisms such as zebrafish, Arabidopsis thaliana, yeast as well as human cell lines. In this study, the utility of a two-component chemical-inducible expression system which was originally developed for the Arabidopsis plant system was investigated in the green microalgae, C. vulgaris UMT-M1 for the expression of the YoeBSpn and PezT toxin from the Gram-positive bacterium, Streptococcus pneumoniae. Both the activator vector, pMDC150 that harbored the constitutive CaMV 35S promoter together with responder vector (pMDC221) cloned with translational fusions of either yoeBSpn-GFP or pezT-GFP, respectively, were co-transformed into C. vulgaris UMT-M1 via Agrobacterium tumefaciens-mediated transformation. The XVE transcription activator encoded on the pMDC150 vector was constitutively expressed under the control of CaMV 35S promoter. In the presence of 17-β-estradiol as the inducer, an XVE-responsive promoter (OlexTATA) readily initiates transcription of the yoeBSpn-GFP and pezT-GFP fusion genes that were cloned separately into the pMDC221 responder vector. Following Agrobacterium-mediated transformation, PCR analysis confirmed that the transgenes were present in the transformed C. vulgaris lines. Upon 17-β-estradiol treatment to express the yoeBSpn-GFP and pezT-GFP fusions, GFP signals were observed in transgenic C. vulgaris cells which showed signs of cellular damage and lysis. Expression of the YoeBSpn and PezT toxins greatly affected the cell viability of the transgenic C. vulgaris cells. This is the first report demonstrating the simultaneous transformation of two vectors into C. vulgaris as well as the functionality of the XVE-based two-component expression system in C. vulgaris. This is also the first demonstration of the lethality of bacterial TA toxins in eukaryotic microalgae as evidenced by the morphological changes and cell lysis of transgenic Chlorella vulgaris subsequent to the activation of YoeB and PezT toxins. The conditional expression of the bacterial toxin in microalgae can be used to develop novel means to efficiently harvest microalgal cellular contents through the lysis of transgenic microalgal cells triggered by toxin activation upon induction with the appropriate signal.